Geochemical Characteristics of Soil Gas and Strong Seismic Hazard Potential in the Liupanshan Fault Zone (LPSFZ). (17th October 2020) - Zhou, Huiling; Su, Hejun; Zhang, Hui; Li, Chenhua; Ma, Dongzheng; Bai, Ronglong
Abstract : Eight soil gas measurements were performed in the Liupanshan fault zone (LPSFZ) to observe the concentration and flux of soil gas radon (Rn) and CO2 in October 2017 and October 2018. By combining the historical strong earthquake background and modern seismic activity of the fault zone, the relation between the geochemical distribution characteristics of soil gas and the seismicity of the fault zone was studied herein. Furthermore, the strong seismic hazard potential of the fault zone was discussed. Results show that the concentration of soil gas Rn and CO2 considerably varies in the northern segment of the LPSFZ and is relatively stable in the southern segment. The spatial distribution of the concentration intensity and flux is strong in the north and weak in the south. However, the southern segment of the LPSFZ has a seismic gap that has not been ruptured by strong earthquakes with Ms ≥ 6.5 for the last 1400 years, whereas the seismic activity in the northern segment is relatively frequent, indicating that the fault zone locking degree of the southern segment is higher than that of the northern segment. This observation is completely consistent with the geochemical characteristic distribution of soil gas. Therefore, the southern segment of the LPSFZ should be considered a hazardous segment, where major or strong earthquakes can occur in the future.